Push-pull plus: reconsidering the drivers of migration - Van Hear, N; Bakewell, O; Long, K (Routledge, 2017)
Drivers can be understood as forces leading to the inception of migration and the perpetuation of movement. This article considers key drivers of migration and explores different ways that they may be configured. We modify existing explanations of migration to generate a framework which we call push-pull plus. To understand migration flows better, analysts could usefully distinguish between predisposing, proximate, precipitating and mediating drivers. Combinations of such drivers shape the conditions, circumstances and environment within which people choose to move or stay put, or have that decision thrust upon them. In any one migration flow, several driver complexes may interconnect to shape the eventual direction and nature of movement. The challenge is to establish when and why some drivers are more important than others, which combinations are more potent than others, and which are more susceptible to change through external intervention. Drawing on Afghan and Somali movements featuring ‘mixed migration’, the article concludes that proximate and mediating drivers, rather than those in the structural and precipitating spheres, appear to offer greater potential for intervention. To be effective, though, migration policy should be understood not simply as a stand-alone lever, but within the wider political economy.